The effect of match congestion on hip adductor squeeze strength in youth rink hockey players - Marcos Quintana-Cepedal; Omar de la Calle; Irene Crespo; María Medina-Sánchez; Miguel del Valle; Hugo Olmedillas (Elsevier, 2024)
Introduction: Groin injuries are common among rink hockey players. Monitoring the main risk factors can reduce the likelihood of suffering such injury. The objective of this study was to evaluate the effect of a competitive congestion period on the squeeze strength of the hip adductor muscles in a group of adolescent rink hockey players, and whether the strength reduction exceeded the injury risk threshold (>15%) for sustaining a groin injury. Materials and Methods: Twenty U-16 athletes (9 females) participated in the study. Eighty-three adductor strength measurements were recorded after 10 games (2109 min of play). Function was assessed using the Sport subscale of the Hip and Groin Outcome Score (HAGOS) questionnaire. A simple linear regression model was used to analyze the accumulated time-strength relationship, and the pre-tournament and post-tournament HAGOS results were compared. Results: The accumulation of games resulted in a significant strength reduction in male players' (R2= 0.27), but not in females. Eighty-five percent of the sample had their strength reduced to values at risk compared to baseline strength, but none of them stopped their activity due to discomfort in the groin region. HAGOS results were not affected by the competitive congestion (p = 0.07-0.48). Conclusion: Match congestion can negatively impact adductor strength. However, there may not be a relationship between strength loss above 15% and the appearance of a groin injury.